Factors contributing to the delaying of electricity bill payment among TNB consumers: a case study at TNB Tanah Merah / Noor Hidayah Mohd Faisal Baskaran - Mohd Faisal Baskaran, Noor Hidayah (2011)
The aim of the study was to examine the factors that contribute to the delaying of electricity bill payment among TNB consumers in Tanah Merah Kelantan. There are three factors being studied, which are: bill presentment, payment method and consumers’ attitude. TNB organisation has been chosen as the unit of analysis for this study. In collecting data, the researcher used both secondary and primary data. Moreover, questionnaires had been used in order to get feedback from the consumers. The researcher had distributed 100 questionnaires and had gotten back 100 respondents’ feedback. The data collected was then tested on its reliability, and then further analyzed using frequency analysis and Pearson Correlation Coefficient. Besides, Regression Analysis was used to test the hypotheses in this study. The findings of this paper suggest that only two factors are significant factors in explaining the reasons of electricity bill payment delaying among TNB consumers in Tanah Merah and one factor is rejected. Based from the results obtained in this study, the researcher suggests some recommendations that can help TNB organisation to improve their bill payment collection and increase the numbers of bill payment collection around Tanah Merah area